Yusuf Al-Qardhawi's Perspective of Ihdad and its Relevance to Career Women's Leave Rights in Bandar Lampung - Firdawaty, Linda; Sukandi, Ahmad; Niaz, Noorjehan Safia; Asnawi, Habib Shulton (IAIN Manado, 2023)
This research aims to analyze Yusuf Al-Qardhawi's views on ihdad and the implementation of career women's leave rights due to the death of their husbands and their relevance to contemporary Islamic family law. This research is a field research study. The informant consisted of the General Manager of the Chandra Supertore Bandar Lampung company, qualitative analysis. Research findings show that Yusuf al Qardhawi is of the view that women who are in ihdad may carry out their professions outside the home, limited to professions permitted by religion, maintaining religious ethics, whether in clothing, walking, talking, avoiding making up, wearing perfume, interacting with the opposite sex. This ability protects the benefit and survival of the family, as is the concept of Maqashid al Syari'ah to protect the soul, religion, mind, lineage, and property. Career women's leave rights due to the death of their husbands are only two days in employment law. However, in its implementation at the Chandra Superstore company, career women generally take one week off. They consist of the right to 2 days of leave plus permission from the company for two days, plus exchanging work schedules with colleagues in the profession. The company still requires its employees to look attractive according to the Company's SOP. Implementing this left-right is still very far from being different from the head criteria in Islamic family law.